1997
DOI: 10.1289/ehp.971051084
|View full text |Cite
|
Sign up to set email alerts
|

Children with moderately elevated blood lead levels: a role for other diagnostic tests?

Abstract: In this study we examined potential limitations of relying excdusively on blood lead (BPb) levels to evaluate children with moderatdy elevated BPb levels (1.21-2.12 pmol/l, or 25-44 pg/dl).We tested the following hypotheses: 1) such children without elevated erythrocyte protoporphyrin (EP) levels (.0.62

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
2
4
1
Order By: Relevance
“…Other studies have reported rates of positive challenge tests comparable to those in our study (15,17,18 …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Other studies have reported rates of positive challenge tests comparable to those in our study (15,17,18 …”
Section: Discussionsupporting
confidence: 90%
“…A low EP level is excellent at identifying such children; only 3% of challenge tests with an EP level < 0.62 pmol/L (< 35 pg/dL) were positive. This finding is comparable to the 4.8% reported by Markowitz et al (15). A decreasing blood lead level is a fair predictor of a negative challenge test; 86% of children whose blood lead level was decreasing (i.e., RATE < 0 pg/dL/day) had a negative challenge test.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…1 In affected children, whose blood lead levels were often greater than 100 µg per deciliter, chelating agents rapidly lowered blood lead levels by brisk diuresis and stopped the progression of lead poisoning to the point of frank encephalopathy. 8,9 This treatment saved lives but did not eliminate the neurologic consequences, which were permanent. Very rarely, if ever, does chelation therapy for such severe lead poisoning reverse or prevent the signs and symptoms of lead-induced neurotoxicity.…”
mentioning
confidence: 99%